2020
DOI: 10.1016/j.sjbs.2020.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesized silver nanoparticles using Caulerpa taxifolia against A549 lung cancer cell line through cytotoxicity effect/morphological damage

Abstract: The Caulerpa taxifolia is excellent marine green algae, which produced enormous bioactive compounds with more biological activities. Also, it is an excellent source for synthesis of Ag NPs with increased bioactivity against various infections. In our study, the marine algae marine algae Caulerpa taxifolia mediated Ag NPs was synthesized effectively. The synthesized Ag NPs was characterized well using UV-spectrometer and X-ray powder diffraction (XRD) and confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Prepared CS/FeO NC induced 50% (IC 50 ) of growth suppression property at the concentration of 82 ± 0.50 µg/mL. Similar to our study, biosynthesized silver nanoparticles from Caulerpa taxifolia also showed the concentration-dependent anti-lung cancer activity [48]. In addition, the A549 cell proliferation was observed using fluorescence microscopy.…”
Section: Anti-proliferative Property Of Cs/feo Ncsupporting
confidence: 83%
“…Prepared CS/FeO NC induced 50% (IC 50 ) of growth suppression property at the concentration of 82 ± 0.50 µg/mL. Similar to our study, biosynthesized silver nanoparticles from Caulerpa taxifolia also showed the concentration-dependent anti-lung cancer activity [48]. In addition, the A549 cell proliferation was observed using fluorescence microscopy.…”
Section: Anti-proliferative Property Of Cs/feo Ncsupporting
confidence: 83%
“…Interestingly, these works are all related to the cytotoxicity evaluation of the A549 cell line. Several studies reported lung cell cytotoxicity in a concentration-dependent manner for small-sized [45,47,49,52] and big-sized [48] AgNPs. Some other authors disclose the time and size-dependent cytotoxicity for this particular cell line for medium-sized AgNPs [50,51].…”
Section: Phytogenic Agnpsmentioning
confidence: 99%
“…The differential gene expression observed among several lung cell types exposed to different AgNP formulations indicates that independently of the coating, size, or cell type, AgNPs impact transcriptional reprogramming of exposed cells. The specific gene expression changes of lung cells exposed to AgNPs can be used as inflammation or lung damage biological biomarkers [14,29,48,49,56,72,73,148,152]. Moreover, AgNPs exert cellular lung death by altering cell cycle, DNA content, and membrane tissue remodeling, further deriving cell death in a cell-type dependent manner.…”
Section: Trojan Horse Mechanism Exerting Lung Cell Death Mainly By P5...mentioning
confidence: 99%
“…Marine-derived natural products, in particular, are potential molecules for the development of anticancer drugs because they may influence multiple pathways, such as immunity, cancer cell death, and tumor growth [ 118 ]. Silver nanoparticles derived from Caulerpa taxifolia showed antitumor efficacy against A549 lung cancer cells [ 119 ]. Necrosis and condensation of A549 cells were shown to be mediated by silver nanoparticles derived from marine algae, suggesting that nanomaterials are relevant for cancer cell research.…”
Section: Marine Bioinspired Nps For Treating Non-infectious Diseasesmentioning
confidence: 99%